Moisture sorption characteristics of kalakand- a traditional Indian dairy product - deshmukh, gajanan panditrao (Indian Journal of Dairy Science, 2017)
The sorption isotherms describe the equilibrium relation between water activity (aw) and moisture content of food at constant temperatures and pressures condition. In present the study the moisture sorption characteristics of Kalakand prepared from standardized milk were investigated by using static gravimetric method, at 15, 25, 350C, over the range of water activity (aw) 0.11 to 0.97. The isotherms obtained were of Type-II (sigmoid) shape. All isotherms show that EMC, at given water activity decreases with increased in temperature. GAB, Caurie, Oswin, Modified Mizrahi and Halsey models were applied to the experimental isotherm data of Kalakand. The suitability of the models tested statistically and compared by determining coefficient root-mean-square error values (% RMS). Out of all five models tested, the GAB model was found most suitable for describing of sorption data which was having least RMS value. The sorption data were analyzed to determine monolayer moisture content as calculated by the best fitted GAB model for desorption and adsorption processes at 15, 25 and 35oC were 5.621, 4.589 & 4.185 and 4.249, 3.520 & 3.177 g/100g solid, respectively.Â